A method for in-situ generation of CuCrZr alloy with nano-precipitated phase
Through electron beam selection melting technology, CuCrZr alloy with nano-precipitation phases was generated in situ during the printing process and strengthened, which solved the problem of uneven distribution of precipitation phases in traditional smelting and casting processes, and achieved the high density and tensile strength of CuCrZr alloy.
Patent Information
- Application Number
- CN202211097481.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-08
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-09-08
AI Technical Summary
When preparing CuCrZr alloys in traditional smelting and casting processes, there are problems such as uneven distribution of precipitation phases, affecting service life and safety.
CuCrZr alloy is prepared by electron beam selection melting technology. CuCrZr alloy with nanoprecipitation phase is generated in situ during the printing process by regulating process parameters, and strengthening is carried out to improve tensile strength.
The density and tensile strength of CuCrZr alloy are improved, which reduces the concentration of thermal stress, reduces the risk of warping and deformation during the manufacturing process, and eliminates subsequent heat treatment processes.
Smart Images

Figure CN116287822B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal material manufacturing, and in particular relates to a method for in-situ generating a CuCrZr alloy with a nano-precipitated phase. Background Art
[0002] Copper is widely used in aerospace, new energy vehicles, precision instruments, integrated circuits, lead frames, liquid rocket engines, high-efficiency heat exchangers and other fields due to its good electrical conductivity, thermal conductivity and excellent mechanical properties. It is one of the key raw materials used in scientific and technological development. The excellent electrical conductivity of copper cannot be replaced by other materials and has become the focus of competition for international high-end materials. Since pure copper has excellent electrical conductivity but is relatively soft, its application in some fields is limited. The alloying of copper is an important factor in improving the mechanical properties of copper materials. Therefore, a new generation of high-strength and high-conductivity CuCrZr alloys has been developed. After years of development, CuCrZr alloys have been applied to various fields.
[0003] However, when using traditional smelting and casting processes to prepare CuCrZr alloys, there are characteristics such as the growth and uneven distribution of the precipitate phase, which will seriously affect the service life and safe service requirements of the CuCrZr alloy. Therefore, it is usually necessary to do a lot of plastic deformation, solution treatment and aging treatment to optimize the size distribution of the precipitate phase to regulate the microstructure and thus improve the performance.
[0004] Selected electron beam melting (SEBM) technology is a forming process for 3D printing metal materials. SEBM specimen construction is mainly divided into three stages: preheating, forming, and self-tempering. High-energy electron beams are used to melt and solidify powder materials layer by layer. The entire process is carried out under high power and high vacuum conditions. This technology can be used to prepare parts with complex geometric shapes, and based on the characteristics of rapid melting and solidification of SEBM molten metal powder, the prepared samples have the characteristics of fine grains, uniform chemical composition, and nano-scale precipitation phases.
[0005] Therefore, the present invention adopts electron beam selective melting technology to prepare CuCrZr alloy to avoid the problems existing in the preparation of traditional smelting and casting processes. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for in-situ generating a CuCrZr alloy having a nano-precipitated phase.
[0007] The technical solution of the present invention is: a method for in-situ generation of a CuCrZr alloy with a nano-precipitated phase, comprising the following steps:
[0008] S1. Electrode rod processing and atomization powder making
[0009] The CuCrZr alloy rods are processed into electrode rods of the specifications required for plasma rotating electrode atomization powder making, and then the CuCrZr alloy spherical powder is prepared by plasma rotating electrode atomization method;
[0010] The CuCrZr alloy bar comprises, by mass percentage, Cr: 0.16-0.25%, Zr: 0.08-0.12%, and the balance is copper;
[0011] S2. Powder treatment
[0012] Screening out CuCrZr alloy spherical powder of required specifications, placing the CuCrZr alloy spherical powder of required specifications in a heating furnace for heating and drying;
[0013] S3. Data scanning
[0014] Constructing a structure model to be printed, and slicing the printed three-dimensional structure model using slicing software, and then scanning each slice layer to obtain data; then importing the data into an electron beam selective area melting forming device, and evacuating a forming chamber in the electron beam selective area melting forming device, and filling the forming chamber with a protective gas;
[0015] The density of the block sample in the structural model is measured, and the microstructure of the block sample is observed using a scanning electron microscope;
[0016] S4, Electron Beam Selective Melting
[0017] The electron beam selective area melting forming device is turned on, the voltage and the grid voltage of the electron beam selective area melting forming device are adjusted, and the substrate is preheated. After the process parameters of the electron beam selective area melting forming processing are set, the electron beam selective area melting forming processing is performed to in-situ generate a CuCrZr alloy part with a nano-precipitated phase;
[0018] S5. Post-processing
[0019] Performing a strengthening treatment on the CuCrZr alloy part with the nano-precipitated phase cooled to 50-70° C. in a protective gas environment, and then performing a surface sandblasting treatment on the CuCrZr alloy part with the nano-precipitated phase to obtain a formed part;
[0020] The strengthening treatment is: high temperature immersion treatment with a mixed salt solution.
[0021] Furthermore, in step S1, the electrode rod of the required specification is a round rod with a diameter of 28-40 mm or a diameter of 70-90 mm and a length of 100-300 mm, the roundness deviation of the round rod is ≤0.05 mm, the straightness deviation is ≤0.1 mm / m, the roughness is ≤1.2 μm, and the density is 99.0%-99.7%.
[0022] The above-mentioned parameters of the electrode rod can improve the powder making quality during the powder making process of the plasma rotating electrode. The length and diameter can better cooperate with the operation of the rotating electrode, thereby obtaining spherical powder with relatively uniform particle size and stability.
[0023] Furthermore, in step S1, the process parameters for preparing CuCrZr alloy spherical powder by the plasma rotating electrode atomization method are as follows: the rotation speed of the electrode rod is 10000-50000 r / min, the feed rate of the electrode rod is 0.5-3.0 mm / s, the melting voltage of the plasma arc is 150-200 V, and the melting current of the plasma arc is 1000-3000 A.
[0024] If the rotation speed of the electrode rod is too fast, flaky powder is likely to be produced, and if the rotation speed is too slow, the powder yield is low; if the voltage and current are too large, turbulent liquid flow is likely to be produced, forming flaky powder; and it is easy to cause partial ablation of low-boiling point elements such as Al and Si; therefore, the use of the above parameters can more efficiently and stably produce powders of the required specifications.
[0025] Furthermore, in step S2, the CuCrZr alloy spherical powder of the required specification is a CuCrZr alloy spherical powder with a particle size distribution of 15 to 106 μm; the heating and drying temperature is 75 to 85° C., and the heating and drying time is 4.5 to 5.5 h.
[0026] The powder in the particle size range can effectively avoid the powder blowing phenomenon during the printing process, and the heating and drying parameters can effectively reduce the moisture inside the CuCrZr alloy spherical powder and remove oil pollutants.
[0027] Furthermore, in step S3, the forming chamber is evacuated to a vacuum degree of >1×10 -3 Pa, and the protective gas is helium.
[0028] Processing parts in the vacuum environment containing protective gas is more conducive to avoiding oxidation and oxygenation during the part processing process, and also avoids the introduction of impurity elements.
[0029] Furthermore, in step S4, the voltage of the electron beam selective melting forming equipment is 59-61KV, and the grid voltage is 290-379V; the substrate is preheated to 100-250°C.
[0030] The preheating step reduces the temperature gradient of powder heating and can reduce the residual stress inside the part.
[0031] Furthermore, in step S4, the process parameters include: the contour line beam current is 4.9-5.1 mA, the scanning speed is 0.15-0.25 m / s; the electron beam current is 15.5-17.0 mA, the scanning speed is 2.0-3.5 m / s, the scanning spacing is 80-110 μm, and the electron beam spot diameter is 95-105 μm.
[0032] The electron beam uses the current, scanning speed and other process parameters to quickly reach the preheating temperature of the powder and then complete the bonding, thereby avoiding the "powder blowing" phenomenon caused by powder collapse.
[0033] Furthermore, in step S3, Auto CAD is used to construct the structure model to be printed, and the three-dimensional structure model printed out using the layering software Magics is sliced, each slice having a thickness of 40 to 70 μm, and the slice layers are scanned by rotating 90° to switch the scanning surface.
[0034] The slice thickness can make the overlap between the slices more compact, and the scanning method can scan the information of the slices more completely.
[0035] Furthermore, in step S5, the strengthening treatment method is:
[0036] The CuCrZr alloy part with the nano-precipitated phase is immersed in the mixed salt solution for 2 to 3 minutes every 5 to 6 minutes, and the temperature of the mixed salt solution is increased to 800 to 850° C. for 40 to 50 minutes, and then kept warm for 20 to 30 minutes. During the insulation, the CuCrZr alloy part with the nano-precipitated phase is always immersed in the mixed salt solution;
[0037] When the CuCrZr alloy part with the nano-precipitated phase is in an immersed state, a magnetic field of 280 to 300 Gs is applied to the mixed salt solution. After the heat preservation is completed, the CuCrZr alloy part with the nano-precipitated phase is taken out and cooled in liquid nitrogen;
[0038] The mixed salt solution comprises, by mass percentage, 20% to 30% of potassium borofluoride, 15% to 20% of potassium fluorotitanate, 2% to 5% of calcium propionate and the balance of water.
[0039] By intermittently dipping the parts in a high-temperature mixed salt solution, the components of the mixed salt solution react completely to generate mixed salts, while the salts penetrate into the parts from the pores of the parts, thereby improving the tensile strength inside the parts.
[0040] After intermittent dipping, the parts are kept warm so that the tensile strength of each part inside the parts is evenly improved;
[0041] Applying magnetic field strength during the part dipping process can shorten the part dipping time and enhance the contact effect of the mixed salt solution inside;
[0042] Cooling the parts in liquid nitrogen after dipping can reduce the temperature as quickly as possible and reduce stress.
[0043] The beneficial effects of the present invention are:
[0044] (1) The present invention uses electron beam selective melting technology to shape CuCrZr alloy powder materials, and does not require steps such as solid solution treatment. By adjusting process parameters, a CuCrZr alloy with a nano-precipitated phase can be in situ generated during the printing process; and the present invention is always in a vacuum state during the printing process, thereby avoiding oxidation of the powder and the introduction of impurity elements.
[0045] (2) The present invention strengthens the CuCrZr alloy parts with nano-precipitated phases by intermittently immersing the CuCrZr alloy parts in a high-temperature mixed salt solution with the assistance of a magnetic field, and keeping the mixed salt solution warm for a period of time, thereby effectively improving the tensile strength of the parts without destroying the plasticity and improving the comprehensive performance of the parts.
[0046] (3) The electron beam selective melting technology used in the present invention can reduce the concentration of thermal stress and reduce the risk of warping and deformation of the formed parts during the manufacturing process; the residual stress of the formed parts is lower, and the subsequent heat treatment process can be omitted. Through this technology, a CuCrZr alloy sample with a density of more than 99% was successfully printed. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 is a formed block sample of Example 1 of the present invention;
[0048] Figure 2 is an optical photograph of the microstructure of the formed block sample of Example 1 of the present invention;
[0049] Figure 3 This is a SEM photograph of the nano-precipitation phase of the formed block sample of Example 1 of the present invention. DETAILED DESCRIPTION
[0050] The present invention is further described in detail below in conjunction with specific implementation methods to better reflect the advantages of the present invention.
[0051] Example 1
[0052] A method for in-situ generation of a CuCrZr alloy having a nano-precipitated phase comprises the following steps:
[0053] S1. Electrode rod processing
[0054] The CuCrZr alloy rods are rolled into electrode rods of the specifications required for plasma rotating electrode atomization powder making, and then the CuCrZr alloy spherical powder is prepared by plasma rotating electrode atomization method;
[0055] The CuCrZr alloy rod material comprises Cr: 0.20%, Zr: 0.10%, and the balance is copper by mass percentage; the electrode rod of the required specification is a round rod with a diameter of 40 mm and a length of 100 mm, the roundness deviation of the round rod is 0.05 mm, the straightness deviation is 0.1 mm / m, the roughness is 1.2 μm, and the density is 99.4%;
[0056] The process parameters of the plasma rotating electrode atomization powder making are: the rotation speed of the electrode rod is 30000r / min, the feed rate of the electrode rod is 2.0mm / s, the melting voltage of the plasma arc is 180V, and the melting current of the plasma arc is 2000A;
[0057] S2. Powder treatment
[0058] Screening out CuCrZr alloy spherical powder of required specifications, placing the CuCrZr alloy spherical powder of required specifications in a heating furnace for heating and drying;
[0059] The required specification of CuCrZr alloy spherical powder is CuCrZr alloy spherical powder with a particle size distribution of 50 to 80 μm; the heating and drying temperature is 80° C., and the heating and drying time is 5 hours;
[0060] S3. Data scanning
[0061] The structure model to be printed was constructed using Auto CAD, and the three-dimensional structure model printed using the layering software Magics was sliced. The thickness of each slice was 55 μm, and the slices were scanned by rotating 90° to switch the scanning surface to obtain data. The data was then imported into the electron beam selective area melting forming equipment, and the forming chamber in the electron beam selective area melting forming equipment was evacuated to a vacuum degree of 1.1×10 -3 Pa, and filling the forming chamber with helium;
[0062] The density of the block sample in the structural model is measured, and the microstructure of the block sample is observed using a scanning electron microscope;
[0063] S4, Electron Beam Selective Melting
[0064] The electron beam selective melting forming device is turned on, the voltage and grid voltage of the electron beam selective melting forming device are adjusted, and the substrate is heated to 170° C. After setting the process parameters of the electron beam selective melting forming process, the electron beam selective melting forming process is performed to in-situ generate a CuCrZr alloy part with a nano-precipitated phase;
[0065] The voltage of the electron beam selective melting forming equipment is 60KV, and the grid voltage is 330V;
[0066] The process parameters include: the contour line beam current is 5 mA, the scanning speed is 0.2 m / s; the electron beam current is 16 mA, the scanning speed is 2.8 m / s, the scanning interval is 95 μm, and the electron beam spot diameter is 100 μm;
[0067] S5. Post-processing
[0068] Performing a strengthening treatment on the CuCrZr alloy part having a nano-precipitated phase cooled to 60° C. in a helium environment, and then performing a surface sandblasting treatment on the CuCrZr alloy part having a nano-precipitated phase to obtain a formed part;
[0069] The specific method of the strengthening treatment is:
[0070] The CuCrZr alloy part with the nano-precipitated phase is immersed in the mixed salt solution for 2.5 minutes every 5.5 minutes, and the temperature of the mixed salt solution is increased to 830° C. for 45 minutes, and then kept warm for 25 minutes. During the keeping warm period, the CuCrZr alloy part with the nano-precipitated phase is always immersed in the mixed salt solution;
[0071] When the CuCrZr alloy part with the nano-precipitated phase is in an immersed state, a magnetic field of 290 Gs is applied to the mixed salt solution, and after the heat preservation is completed, the CuCrZr alloy part with the nano-precipitated phase is taken out and cooled in liquid nitrogen;
[0072] The mixed salt solution comprises, by mass percentage, 25% potassium borofluoride, 18% potassium fluorotitanate, 4% calcium propionate and the remainder water.
[0073] Example 2
[0074] The difference between this embodiment and embodiment 1 is that in step S1, the CuCrZr alloy rod comprises, by mass percentage, Cr: 0.16%, Zr: 0.08%, and the balance is copper;
[0075] The rotation speed of the electrode rod is 10000 r / min, the feeding rate of the electrode rod is 0.5 mm / s, the melting voltage of the plasma arc is 150 V, and the melting current of the plasma arc is 1000 A.
[0076] Example 3
[0077] The difference between this embodiment and embodiment 1 is that in step S1, the CuCrZr alloy rod comprises, by mass percentage, Cr: 0.25%, Zr: 0.12%, and the balance is copper;
[0078] The rotation speed of the electrode rod is 50000 r / min, the feeding rate of the electrode rod is 3.0 mm / s, the melting voltage of the plasma arc is 200 V, and the melting current of the plasma arc is 3000 A.
[0079] Example 4
[0080] The difference between this embodiment and embodiment 1 is that in step S2, the CuCrZr alloy spherical powder of the required specification is the CuCrZr alloy spherical powder with a particle size distribution of 15 to 50 μm; the heating and drying temperature is 75° C., and the heating and drying time is 4.5 h.
[0081] Example 5
[0082] The difference between this embodiment and embodiment 1 is that in step S2, the CuCrZr alloy spherical powder of the required specification is the CuCrZr alloy spherical powder with a particle size distribution of 80 to 106 μm; the heating and drying temperature is 85° C., and the heating and drying time is 5.5 h.
[0083] Example 6
[0084] The difference between this embodiment and embodiment 1 is that, in step S4, the voltage of the electron beam selective melting forming equipment is 59KV, and the grid voltage is 290V; the substrate is heated to 100°C;
[0085] The contour line beam current is 4.9mA, and the scanning speed is 0.15m / s; the electron beam current is 15.5mA, the scanning speed is 2.0m / s, the scanning spacing is 80μm, and the electron beam spot diameter is 95μm.
[0086] Example 7
[0087] The difference between this embodiment and embodiment 1 is that, in step S4, the voltage of the electron beam selective melting forming equipment is 61KV, and the grid voltage is 379V; the substrate is heated to 250°C;
[0088] The contour line beam current is 5.1mA, and the scanning speed is 0.25m / s; the electron beam current is 17.0mA, the scanning speed is 3.5m / s, the scanning spacing is 110μm, and the electron beam spot diameter is 105μm.
[0089] Example 8
[0090] The difference between this embodiment and embodiment 1 is that in step S3, the slice thickness of each slice is 40 μm.
[0091] Example 9
[0092] The difference between this embodiment and embodiment 1 is that in step S3, the slice thickness of each slice is 70 μm.
[0093] Example 10
[0094] The difference between this embodiment and embodiment 1 is that, in the strengthening treatment, the CuCrZr alloy part with the nano-precipitated phase is immersed in the mixed salt solution for 2 minutes every 6 minutes, and then kept warm for 20 minutes.
[0095] Embodiment 11
[0096] The difference between this embodiment and embodiment 1 is that, during the strengthening treatment, the CuCrZr alloy part with the nano-precipitated phase is immersed in the mixed salt solution for 3 minutes every 5 minutes, and then kept warm for 30 minutes.
[0097] Example 12
[0098] The difference between this embodiment and embodiment 1 is that, during the strengthening treatment, the temperature of the mixed salt solution is raised to 800° C., and the heating time is 40 minutes.
[0099] Embodiment 13
[0100] The difference between this embodiment and embodiment 1 is that, during the strengthening treatment, the temperature of the mixed salt solution is raised to 850° C., and the heating time is 50 minutes.
[0101] Embodiment 14
[0102] The difference between this embodiment and embodiment 1 is that, during the strengthening process, the magnetic field strength is 280 Gs.
[0103] Embodiment 15
[0104] The difference between this embodiment and embodiment 1 is that, during the strengthening process, the magnetic field strength is 300 Gs.
[0105] Example 16
[0106] The present embodiment is different from the embodiment 1 in that, in the strengthening treatment, the mixed salt solution comprises, by mass percentage, 20% potassium borofluoride, 15% potassium fluorotitanate, 5% calcium propionate and the remainder water.
[0107] Embodiment 17
[0108] The present embodiment is different from the embodiment 1 in that, in the strengthening treatment, the mixed salt solution comprises, by mass percentage, 30% potassium borofluoride, 20% potassium fluorotitanate, 2% calcium propionate and the remainder water.
[0109] Experimental example
[0110] The CuCrZr alloy prepared in Example 1 ( Figure 1 ) for metallographic examination and electron microscope scanning, and obtain Figure 2 The microstructure diagram shown, Figure 3 SEM images shown; according to Figure 2 , 3 It can be observed that the CuCrZr alloy with nano-precipitated phase is in-situ generated by the method of the present invention, and has high density and excellent performance;
[0111] For the CuCrZr alloy prepared in each embodiment, the Archimedes drainage method was used to measure the density. The density of each embodiment was measured 3 times, and the average value of the 3 measurement results was taken as the density measurement result of the embodiment. The specific exploration is as follows:
[0112] 1. Investigate the effect of Examples 1-9 on the density of the prepared CuCrZr alloy.
[0113] Taking Examples 1-9 as comparison, the results are shown in Table 1:
[0114] Table 1 Density test table of each sample of Examples 1-9
[0115] Group Density Example 1 99.6% Example 2 99.1% Example 3 99.7% Example 4 99.3% Example 5 99.8% Example 6 99.1% Example 7 99.5% Example 8 99.4% Example 9 99.3%
[0116] It can be seen from the results in Table 1 that the parameters involved in Examples 1-9 have a certain influence on the density of the prepared CuCrZr alloy, and by comparison, it can be seen that the density of Example 3 and Example 5 is relatively high, but the parameters required for the plasma rotating electrode in Example 3 are larger and the power is larger; the required temperature in Example 5 is higher and the drying time is longer; and the effect improvement of Examples 3 and 5 relative to Example 1 is relatively small. Therefore, from the perspective of economy, the density of the CuCrZr alloy prepared by the parameter design of Example 1 is relatively better.
[0117] The samples of Examples 1, 10-17, and Comparative Examples 1-4 were placed in a material performance testing machine for tensile testing to determine their tensile strengths, and the tensile strength improvement rates of each example compared to Example 1 were calculated. The specific research is as follows:
[0118] 2. Investigate the effect of strengthening treatment on the density and tensile strength of the prepared CuCrZr alloy.
[0119] Taking Examples 10-17 and Comparative Examples 1-4 as comparison, the results are shown in Table 2:
[0120] Table 2 Density and tensile strength improvement rate test table of each sample of Examples 10-17 and Comparative Examples 1-4
[0121]
[0122]
[0123] The difference between Control Example 1 and Example 1 is that the mixed salt solution includes, by mass percentage, 30% potassium borofluoride, 20% potassium fluorotitanate and the balance water; as can be seen from the data in Table 2, when the mixed salt solution lacks calcium propionate, the density and tensile strength are both reduced relative to Examples 1 and 16-17;
[0124] The difference between Control Example 2 and Example 1 is that no additional magnetic field is applied. It can be seen from the data in Table 2 that when there is no magnetic field, the density and tensile strength are both reduced relative to Examples 1 and 14-15.
[0125] The difference between Control Example 3 and Example 1 is that the CuCrZr alloy part with nano-precipitated phase is immersed in the mixed salt solution until the end of the heat preservation; it can be seen from the data in Table 2 that when the immersion rule of the CuCrZr alloy part with nano-precipitated phase in the mixed salt solution is changed, the density and tensile strength are both reduced relative to Examples 1 and 10-11;
[0126] The difference between Comparative Example 4 and Example 1 is that the surface of the CuCrZr alloy part with nano-precipitated phase is directly sandblasted without strengthening treatment. It can be seen from the data in Table 2 that when the strengthening treatment step is missing, the density and tensile strength are both reduced compared with Examples 1 and 10-17.
[0127] Therefore, it can be concluded from the results in Table 2 that the strengthening treatment improves the density and tensile strength of the CuCrZr alloy; it can be seen from the data of Examples 14-15 that too large or too small magnetic field intensity will reduce the density and tensile strength of the CuCrZr alloy; it can be seen from the data of Examples 16-17 that the component ratio of the mixed salt solution will also affect the performance of the CuCrZr alloy;
[0128] Although the density and tensile strength of Examples 11 and 13 are greatly improved, the insulation time of the CuCrZr alloy parts with nano-precipitated phase in Example 11 is longer, and the mixed salt solution temperature required for Example 13 is higher and the heating time is longer, but the improvement of the effects of Examples 11 and 13 relative to Example 1 is small. Therefore, from the perspective of economy, the effect is relatively better under the parameter design of Example 1.
Claims
1. A method for in-situ generation of a CuCrZr alloy having a nano-precipitated phase, characterized in that: The following steps are involved: S1. Electrode rod processing and atomization powder making The CuCrZr alloy rods are processed into electrode rods of the specifications required for plasma rotating electrode atomization powder making, and then the CuCrZr alloy spherical powder is prepared by plasma rotating electrode atomization method; The CuCrZr alloy bar comprises, by mass percentage, Cr: 0.16-0.25%, Zr: 0.08-0.12%, and the balance is copper; S2. Powder treatment Screening out CuCrZr alloy spherical powder of required specifications, placing the CuCrZr alloy spherical powder of required specifications in a heating furnace for heating and drying; S3. Data scanning Construct the required printed structural model, slice the printed three-dimensional structural model using slicing software, and then scan each slice layer to obtain data; Then, the data is imported into an electron beam selective area melting forming device, a forming chamber in the electron beam selective area melting forming device is evacuated, and a protective gas is filled into the forming chamber; The density of the block sample in the structural model is measured, and the microstructure of the block sample is observed using a scanning electron microscope; S4, Electron Beam Selective Melting The electron beam selective area melting forming device is turned on, the voltage and the grid voltage of the electron beam selective area melting forming device are adjusted, and the substrate is preheated. After the process parameters of the electron beam selective area melting forming processing are set, the electron beam selective area melting forming processing is performed to in-situ generate a CuCrZr alloy part with a nano-precipitated phase; S5. Post-processing Performing a strengthening treatment on the CuCrZr alloy part with the nano-precipitated phase cooled to 50-70° C. in a protective gas environment, and then performing a surface sandblasting treatment on the CuCrZr alloy part with the nano-precipitated phase to obtain a formed part; The method of the strengthening treatment is: The CuCrZr alloy part with the nano-precipitated phase is immersed in the mixed salt solution for 2 to 3 minutes every 5 to 6 minutes, and the temperature of the mixed salt solution is increased to 800 to 850° C. for 40 to 50 minutes, and then kept warm for 20 to 30 minutes. During the insulation, the CuCrZr alloy part with the nano-precipitated phase is always immersed in the mixed salt solution; When the CuCrZr alloy part with the nano-precipitated phase is in an immersed state, a magnetic field of 280 to 300 Gs is applied to the mixed salt solution. After the heat preservation is completed, the CuCrZr alloy part with the nano-precipitated phase is taken out and cooled in liquid nitrogen; The mixed salt solution comprises, by mass percentage, 20% to 30% of potassium borofluoride, 15% to 20% of potassium fluorotitanate, 2% to 5% of calcium propionate and the balance of water.
2. The method for in-situ generation of a CuCrZr alloy having a nano-precipitated phase according to claim 1, characterized in that: In step S1, the electrode rod of the required specification is a round rod with a diameter of 28-40 mm or a diameter of 70-90 mm and a length of 100-300 mm, the roundness deviation of the round rod is ≤0.05 mm, the straightness deviation is ≤0.1 mm / m, the roughness is ≤1.2 μm, and the density is 99.0%-99.7%.
3. The method for in-situ generation of a CuCrZr alloy having a nano-precipitated phase according to claim 1, characterized in that: In step S1, the process parameters for preparing CuCrZr alloy spherical powder by the plasma rotating electrode atomization method are as follows: the rotation speed of the electrode rod is 10000-50000 r / min, the feed rate of the electrode rod is 0.5-3.0 mm / s, the melting voltage of the plasma arc is 150-200 V, and the melting current of the plasma arc is 1000-3000 A.
4. The method for in-situ generation of a CuCrZr alloy having a nano-precipitated phase according to claim 1, characterized in that: In step S2, the CuCrZr alloy spherical powder of the required specification is a CuCrZr alloy spherical powder with a particle size distribution of 15 to 106 μm; the heating and drying temperature is 75 to 85° C., and the heating and drying time is 4.5 to 5.5 hours.
5. The method for in-situ generation of a CuCrZr alloy having a nano-precipitated phase according to claim 1, characterized in that: In step S3, the thickness of each slice is 40-70 μm, and the forming chamber is evacuated to a vacuum degree of >1×10 - 3 Pa, and the protective gas is helium.
6. The method for in-situ generation of a CuCrZr alloy having a nano-precipitated phase according to claim 1, characterized in that: In step S4, the voltage of the electron beam selective melting forming equipment is 59-61KV, the grid voltage is 290-379V; and the substrate is preheated to 100-250°C.
7. The method for in-situ generation of a CuCrZr alloy having a nano-precipitated phase according to claim 1, characterized in that: In step S4, the process parameters include: contour line beam current is 4.9-5.1 mA, scanning speed is 0.15-0.25 m / s; electron beam current is 15.5-17.0 mA, scanning speed is 2.0-3.5 m / s, scanning spacing is 80-110 μm, and electron beam spot diameter is 95-105 μm.
8. The method for in-situ generation of a CuCrZr alloy having a nano-precipitated phase according to claim 1, characterized in that: In step S3, Auto CAD is used to construct the structure model to be printed, and the three-dimensional structure model printed out using the layering software Magics is sliced. The thickness of each slice is 40 to 70 μm, and the slice layers are scanned by rotating 90° to switch the scanning surface.
Citation Information
Patent Citations
Ultra-short period high-strength and high-ductility nickel-aluminum-bronze alloy and preparing method
CN109628772A
Preparation method of CuCrZr alloy powder for three-dimensional (3D) printing
CN112719279A